International Productivity Patterns: Accounting for Input Quality, Infrastructure, and Research - Craig, Barbara J.; Pardey, Philip G.; Roseboom, Johannes (Wiley, 1997)
In this paper, we present measures of land and labor productivity for a group of ninety‐eight developed and developing countries using an entirely new data set with annual observations spanning the past three decades. The substantial cross‐country and intertemporal variation in productivity in our sample is linked to both natural and economic factors. We extend previous work by dealing with multiple sources of systematic measurement error in conventional agricultural inputs. The mix of conventional inputs, indicators of quality of agricultural inputs, and the amount of publicly provided infrastructure are all significant in explaining observed cross‐sectional differences in productivity patterns.